Spatio-temporal variation of aerosols in ENSO events over Western India using satellite data. Issue 2 (2021) - Patel, Vikas K; Taksal, Prakash A; Londhe, Digambar S; Katpatal, Yashwant B
Abstract : The spatial variation of the average aerosol optical depth (AOD) at 555 nm obtained from the multi-angle imaging spectroradiometer satellite sensor over India for 2000–2016 illustrates that Western India shows a relatively lower aerosol loading compared with the northern and eastern parts of India. Among the seasonal variations of the average AOD, spring shows a higher aerosol loading, particularly over Jodhpur (0.518) and Kota (0.518), and fall shows the least. In spring, these variations may be due to the meteorological conditions that bring a large quantity of dust and other types of aerosols in the atmosphere of Western India. Temporal variation of AOD indicates that in 2006, abrupt change in AOD (<0.2) was observed over all the cities. Among all cities, Mumbai shows strong increasing trends during 2000–2016 with a Sen's slope of 0.009. Overall, the study concludes that compared with La Niña years, El Niño years correspond to a higher aerosol loading over Western India, primarily over Surat (0.357), Mumbai (0.349) and Jodhpur (0.334).